2017
DOI: 10.1039/c6ta10094e
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Ni–Fe oxide multi-composite hollow nanocages for efficient electrocatalytic water oxidation reactions

Abstract: The mesoporous NiO/NiFe2O4multi-composite hollow nanocage electrodes are fabricated and achieve a low overpotential (303 mV at 10 mV cm−2) and Tafel plot (58.5 mV dec−1), respectively, and excellent cycling stability (12 h) as an anode material for oxygen evolution reaction, holding great promise for water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…The efficiency and performance of the present catalytic electrodes are comparable or superior to the powder electrocatalysts and catalytic electrodes based on [Ni,Fe]O nanoparticles reported earlier (and also commercially available catalysts like Ir/C and IrO 2 ) (Table S5). [24] The advantage of our strategy in terms of the ease and simplicity of catalyst electrode fabrication is revealed by the comparison with earlier reported methods involving temperatures up to 500°C and multiple steps with processing times ranging from 3-48 h. [27,[40][41][42][43][44] Even though electrodeposition is a simple approach and provides electrocatalysts with high efficiency and extended stability seen in chronoamperometric experiments, careful examination of the electrodes have revealed liberation of iron from the anode and its deposition on the cathode; [2] such catalyst composition changes are detrimental for practical applications. In some cases, dissolution of the surface-bound catalyst had to be compensated by adding the metal ions in the electrolyte.…”
Section: Communicationsmentioning
confidence: 99%
“…The efficiency and performance of the present catalytic electrodes are comparable or superior to the powder electrocatalysts and catalytic electrodes based on [Ni,Fe]O nanoparticles reported earlier (and also commercially available catalysts like Ir/C and IrO 2 ) (Table S5). [24] The advantage of our strategy in terms of the ease and simplicity of catalyst electrode fabrication is revealed by the comparison with earlier reported methods involving temperatures up to 500°C and multiple steps with processing times ranging from 3-48 h. [27,[40][41][42][43][44] Even though electrodeposition is a simple approach and provides electrocatalysts with high efficiency and extended stability seen in chronoamperometric experiments, careful examination of the electrodes have revealed liberation of iron from the anode and its deposition on the cathode; [2] such catalyst composition changes are detrimental for practical applications. In some cases, dissolution of the surface-bound catalyst had to be compensated by adding the metal ions in the electrolyte.…”
Section: Communicationsmentioning
confidence: 99%
“…[8][9][10] For instance, Sumboja et al 8 designed NiMn layered double hydroxides as an efficient oxygen evolution reaction electrocatalyst. In another report, Kang et al 11 demonstrated the activity of NiFe-oxide toward the water oxidation reaction. Despite satisfactory performances, these support-free catalysts suffer from active centre agglomeration and poor electronic conductivity issues, affecting their long-term stability.…”
Section: Introductionmentioning
confidence: 96%
“…Despite satisfactory performances, these support-free catalysts suffer from active centre agglomeration and poor electronic conductivity issues, affecting their long-term stability. [11][12][13][14] A solution for the conductivity issue is to modulate the electronic structure by in situ anchoring these transition metal oxides/ hydroxides over cost-effective conducting supports. 15,16 Among various cost-effective conducting supports, carbon-based materials with electrochemically favourable characteristics, i.e., high electronic conductivity and surface area, have emerged as universal choices in the electrocatalysis eld.…”
Section: Introductionmentioning
confidence: 99%
“…ii) The iron doping may tune the available active surface sites and modify the electronic structure of the catalyst materials, leading to the enhanced electrocatalytic activity . iii) The porous characteristic of FeS–Ni 3 S 2 /NF nanosheets is conducive to the mass transport, ion permeation, and gas release during the catalytic process . iv) The 3D‐interconnected nanosheet structure with high internal porosity could provide the high electrochemical active area and fast channels for charge/mass transport, and finally accelerating the OER process.…”
Section: Resultsmentioning
confidence: 99%
“…PBAs are considered as a promising class of materials because of 1) the 3D open framework with large interstitial sites; 2) the open, low strain, and tunable skeleton; 3) their adjustable composition, good structure, and chemical stability; and 4) their special thermal properties and unique reactivity . When PBAs are applied for electrocatalysis, the porous PBA‐derived materials with open diffusion channels, well‐defined structure, and large surface area could be synthesized by taking PBAs as templates or precursors, such as transition metal sulfides, selenides, phosphides, nitrides, and oxides . The specific structure of these porous PBA‐derived materials is essential in providing rapid electron and electrolyte transportation pathway and improving the electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%